Analysis and Optimization of Delamination Factor for Microwaved Cured Pineapple Leaf Fiber Polymer Composite through ANOVA Analysis - Saha, Manabendra; Singh, Hari; Srivastava, Vivek; Singh, Manoj Kumar (Applied Science and Engineering Progress, 2024)
Natural fiber-reinforced composites are quickly replacing other materials as the material of choice for various engineering applications because of their high specific strength, low weight, and affordability. Additionally, natural composites come in various forms and are environmentally benign. In particular, the composite needs to be drilled to put the pieces together. The entry and exit levels of the holes are prone to damage during the drilling process. In the present work, Low-density polyethylene (LDPE) was combined with pineapple leaf fiber (PALF) mat after first undergoing a chemical treatment in this investigation. Microwave curing was applied for fabricating the natural fiber composite with the three specified process parameters i.e., microwave power, % of NaOH solution, and weight percentage of treated fiber. After fabrication, the composite delamination factor and modified delamination factor were determined for evaluating the crack propagation after the drilling operation. At constant speed, the feed and diameter of the drill were used for making the drill in different samples. A CNC drilling machine was used to drill the constructed structure at various input parameters. Using the Taguchi approach, the entire work was analyzed. A tensile test was conducted to estimate the strength of the samples with specific parameters. The tensile strength increases up to 24.34 MPa. ANOVA analysis was used to find the best combination and affecting factors. It was observed that the weight percentage of the treated fiber mat has a maximum contribution percentage of 61 % for the processing of natural fiber polymer composite.